THE IMPLEMENTATION OF THE CHARACTER EDUCATION STRENGTHENING PROGRAM AT STATE JUNIOR HIGH SCHOOL 4 BINJAI, NORTH SUMATRA - Irin Oktaviani; Februati Trimurni (Yayasan Wayan Marwan Pulungan, 2026)
This study investigates the implementation of the Character Education Strengthening Program at State Junior High School 4 Binjai, Indonesia. The research aims to analyze how the principles of organization, interpretation, and application interact to support the effectiveness of the program in shaping students’ moral and social behavior. Using a qualitative descriptive design, data were collected through observations, in-depth interviews, and document analysis involving teachers, students, and school administrators. The findings reveal that the success of the program depends on the coherent integration of structural, pedagogical, and behavioral dimensions. The organizational framework provides clear coordination and shared responsibility among school stakeholders, while teachers play a central role in interpreting character values into daily educational practices. The consistent application of the five core values like religiosity, nationalism, independence, cooperation, and integrity has fostered a positive school culture and improved students’ moral awareness. Furthermore, collaboration between the school, parents, and community enhances the sustainability of the program. The study concludes that character education becomes effective when implemented as a holistic moral ecosystem rather than a stand-alone policy. The findings emphasize the importance of leadership, teacher capacity, and community participation in cultivating ethical, disciplined, and socially responsible youth. This research contributes to the broader discourse on education reform and provides strategic insights for policymakers to strengthen character-based learning across schools in Indonesia.